Terms of optimization of financial support for the development of defense enterprises - A. Z. Namitulina (Путеводитель предпринимателя)
Military-industrial complex is now in a state of the resource, structural and technological and personnel reform. Idea of the defense industry as market actors and the role of government priorities in the creation of conditions of optimal allocation offinancial support in the industry. Reforming is carried out in an environment where the value of the state has increased significantly in comparison with the control of defense enterprises. Thus, the reform involves not only an improvement in the economy, but also in the defense through effective funding of defense enterprises.